Rossi's principles of transfusion medicine - Rossi, Ennio Claudio , 1931-; Simon, Toby L. (Wiley-Blackwell/AABB Press, 2009)
A practical reference on transfusion science and medicine. It features chapters on the measurement of cell kinetics, obstetric transfusion practice, cord blood, transfusion alternatives and regenerative medicine.